Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan (studi kasus : Klinik Palapa Dentis JAkarta Selatan) - Islami, Vina (www.bsi.ac.id, 2018)
Services is one of the business activities in which the services are basically all economic activity that results were not a product in a physical form or construction. In the era of globalization, the dynamics of the business world is getting harder and tighter included in the health care field. With the increasing quality of the service, the service functions in a dental clinic or the health sector needs to be improved in order to become more effective and efficient and give satisfaction to the patient and society. The more advanced the renewal in the field of technology, the field of health services has also increased, the field of modern infrastructure and facilities as well as being more accurate in the field of services. In connection with such matters, besides the quality of health services must be prioritized, service quality must also be considered again. Therefore, patients in need of quality health care services with satisfactory service. Palapa Dentists dental clinic (Klinik Dr. drgAnggraeni SP, KG) is one company that is engaged in services, especially health. Key words : Service Quality, Satisfaction